NILAI KEPENTINGAN BUDAYA KEANEKARAGAMAN JENIS TUMBUHAN BERGUNADI HUTAN DATARAN RENDAH BODOGOL, SUKABUMI, JAWA BARAT - Mulyati Rahayu; Y Purwanto; Siti Susiarti (BERITA BIOLOGI, 2012)
Index Cultural Significance (ICS) of useful plants diversity in ethnobotanical study is an importance step, such as activity strategy which have subsystem aspect and traditional classification. Ethnobotany study in Bodogol lowland forest, West Java recorded more than 200 useful plants species within 3 times visits in 2009 to 2010. Data collection was done by “walk in the wood”,interview method, direct observation in permanent plots and estimation of Index Cultural Significance (ICS) form.Result of the study indicated that indigenous people around Bodogol lowland forest has good knowledge about biodiversity around them. Based on interview method, this study showed that indexs cultural significance of useful plants in this area was in the range of 0.5 and 86. Kawung {Arenga pinnata (Wurmb) Merr.} has highest ICS whilst Acung leutik (Arisaema filiforme Bl.) is the lowest.